ABOUT THE "TENDER" APPROVAL IN THE FINANCIAL SECTOR IN UZBEK - Salaeva Gulasal Gayratbek kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article is given some borrowed words from English languages.